2016
DOI: 10.29252/ijrm.14.7.5
|View full text |Cite
|
Sign up to set email alerts
|

Modified natural cycle frozen-thawed embryo transfer in patients with repeated implantation failure: An observational study

Abstract: Background:Natural endometrium in Frozen-thawed Embryo Transfer (FET) may have some benefits upon implantation in patients with Repeated Implantation Failure (RIF). It might be due to possible differences between natural and stimulated endometrial growth factors and cytokins secretions.Objective:The objective of this study was to compare the pregnancy rate of FET on modified natural cycle versus hormone replacement therapy (HRT) cycle endometrium in patients with RIF. Materials and Methods:In this observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As stated before, GH adjuvant therapy was clinically widely used in poor ovarian responders (7, 8, 10, 11, 14, 16, 19, 6063, 67–76), poor quality of embryos (16, 17, 67, 70, 74, 77), improper endometrial reaction (5, 12, 56, 78, 79) and repeated implantation failure (1, 63, 8082). When it is used in patients with repeat implantation failure which is defined as failure of pregnancy despite implantation of a high-quality embryo at least three times or of over 10 embryos on repeat implantation failure (1, 63, 8082), the mechanism of this action is, as stated before, related to GH stimulating proliferation and differentiation of granulosa cells, increasing production of estradiol in both early and late follicular development for animal and human ovaries, enhancing effect of FSH on the development of ovarian follicles and improving endometrial thickness (82, 98100). A recent randomized controlled clinical trial performed in China of GH co-treatment on controlled ovarian stimulation in normal ovarian response women showed significantly ( P < 0.05) higher two pronuclei rate (33.92 vs. 30.92%) and higher quality embryo rate (63.4 vs. 59.33%) besides significantly increased number of embryos available (3.79 ± 2.74 vs. 2.90 ± 2.12, P < 0.001) and higher endometrial thickness on hCG day (11.96 ± 2.24 vs. 11.62 ± 2.81, P = 0.036) in 781 patients receiving GH of 1IU/4IU administered daily since day two of the previous cycle or day two in accordance with controlled ovarian stimulation until hCG trigger in comparison with the control group without GH adjuvant therapy (79).…”
Section: Subjects and Benefits Of Gh Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…As stated before, GH adjuvant therapy was clinically widely used in poor ovarian responders (7, 8, 10, 11, 14, 16, 19, 6063, 67–76), poor quality of embryos (16, 17, 67, 70, 74, 77), improper endometrial reaction (5, 12, 56, 78, 79) and repeated implantation failure (1, 63, 8082). When it is used in patients with repeat implantation failure which is defined as failure of pregnancy despite implantation of a high-quality embryo at least three times or of over 10 embryos on repeat implantation failure (1, 63, 8082), the mechanism of this action is, as stated before, related to GH stimulating proliferation and differentiation of granulosa cells, increasing production of estradiol in both early and late follicular development for animal and human ovaries, enhancing effect of FSH on the development of ovarian follicles and improving endometrial thickness (82, 98100). A recent randomized controlled clinical trial performed in China of GH co-treatment on controlled ovarian stimulation in normal ovarian response women showed significantly ( P < 0.05) higher two pronuclei rate (33.92 vs. 30.92%) and higher quality embryo rate (63.4 vs. 59.33%) besides significantly increased number of embryos available (3.79 ± 2.74 vs. 2.90 ± 2.12, P < 0.001) and higher endometrial thickness on hCG day (11.96 ± 2.24 vs. 11.62 ± 2.81, P = 0.036) in 781 patients receiving GH of 1IU/4IU administered daily since day two of the previous cycle or day two in accordance with controlled ovarian stimulation until hCG trigger in comparison with the control group without GH adjuvant therapy (79).…”
Section: Subjects and Benefits Of Gh Treatmentmentioning
confidence: 98%
“…However, some randomized controlled trials discouraged the use of GH in IVF because no definitive benefits have been demonstrated in increasing the live birth rate for poor responders (18, 19), but careful evaluation of these trials showed severe drawbacks as stated before. Up to now, GH has been widely applied in the reproduction area but primarily for poor ovarian responders (7, 8, 10, 11, 14, 16, 19, 6063, 67–76), poor quality of embryos (16, 17, 67, 70, 74, 77), improper endometrial reaction (5, 12, 56, 78, 79) and repeated failure of embryo transfer (1, 63, 8082).…”
Section: Application Of Gh In Ivfmentioning
confidence: 99%
“…A study by Arefi et al. ( 23 ) showed that modified natural cycles led to better pregnancy outcomes in repeated implantation failure (RIF) patients. However, a study by 7 concluded that the clinical pregnancy outcome of mNC-FET cycles was obviously worse than that of NC-FET cycles, which might be related to the population heterogeneity, the timing of hCG induction and the differences in luteal support protocols ( 7 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, one of the other common methods for endometrium preparation is adding GnRH to hormone supplements, or with follicle-stimulating drugs such as Clomiphene Citrate ( Gelbaya et al ., 2006 ; El-Toukhy et al ., 2004 ; Arefi et al ., 2016 ; Peeraer et al ., 2015 ). Modification of physiologic endometrium concentration, the concern of hormonal exposure in the uterus, greater drug doses required, hormone complications and high treatment cost were considered as disadvantages of hormonally manipulated protocols.…”
Section: Introductionmentioning
confidence: 99%